Regional Economic Outlook, May 2006, Sub-Saharan Africa. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2006)
Prepared by the Policy Wing of the IMF African Department, and published twice a year in English and French, Regional Economic Outlook: Sub-Saharan Africa analyzes economic performance and short-term prospects of the 44 countries covered by the Department. Topics examined in recent volumes include responses to exogenous shocks, growth performance and growth-enhancing policies, the effectiveness of regional trade arrangements, macroeconomic implications of scaled-up aid, financial sector development, and fiscal decentralization. Detailed country data, grouped by oil-exporting and -importing countries and by subregion, are provided in an appendix and a statistical appendix, and a list of relevant publications by the African Department is included.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet